PAUL, THE MAN OF THREE WORLDS: STILL INSPIRING THE CHURCH ACROSS FRONTIERS - Wessels, J. M. (Scriptura, 2010)
Paul's cultural heritage is often reduced to his Pharisaic background as a Jew. This article not only looks into Paul's broader Graeco-Roman background, but also at the way in which his conversion and subsequent life as a follower of Jesus Christ influenced the way he looked upon his cultural background. This paper also questions the lack of interest from African scholars in Paul's rich cultural background and the way that he utilised it in his ministry. The article concludes with exploratory suggestions for the interpretation of the cross-cultural Paul for the present-day multi-cultural context in Southern Africa.